Laser Microprinting of Transparent and Weakly Absorbing Solutions - Serra, P.; Patrascioiu, A.; Palla-Papavlu, A.; Fernández-Pradas, J.M.; Morenza, J.L. (ALT Proceedings, 2026)
A laser-based technique for printing transparent andweakly absorbing liquids is developed. Its principleof operation relies in the tight focusing of shortlaser pulses inside the liquid and close to its freesurface, in such a way that the laser radiation isabsorbed in a tiny volume around the beam waist,with practically no absorption in any other locationalong the beam path. If the absorbed energyovercomes the optical breakdown threshold, acavitation bubble is generated, and its expansionresults in the propulsion of a small fraction of liquidwhich can be collected on a substrate, leading to theprinting of a microdroplet for each laser pulse. Thetechnique does not require the preparation of theliquid in thin film form, and its forward mode ofoperation imposes no restriction concerning theoptical properties of the substrate. We demonstratethat the technique is capable of printingmicrodroplets with good resolution, reproducibilityand control, and analyze the influence of the mainprocess parameters. The mechanisms of liquidprinting are also investigated: time-resolvedimaging provides a clear picture of the dynamics ofliquid transfer which allows understanding the mainfeatures observed in the printed droplets.